2019
DOI: 10.1182/blood-2018-07-863233
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sirt-1 controls GVHD by inhibiting T-cell allo-response and promoting Treg stability in mice

Abstract: K E Y P O I N T S l Deficiency of Sirt-1 reduces T-cell pathogenicity in GVHD by enhancing p53 acetylation in T cells and promoting iTreg stability. l Treatment with a Sirt-1 inhibitor reduces Tfh generation, B-cell activation, and plasma cell differentiation during cGVHD development.Graft-versus-host disease (GVHD) remains one of the major complications after allogeneic bone marrow transplantation (allo-BMT). Sirtuin-1 (Sirt-1) plays a crucial role in various biological processes including cellular senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 59 publications
1
54
0
Order By: Relevance
“…That is, the SIRT1/ERK pathway was essential for Que protecting against INH‐induced apoptosis. In addition to apoptosis, immune response is another important feature in INH‐induced hepatotoxicity and SIRT1/ERK is also known as a potential regulator of immune process . Hence, SIRT1/ERK‐mediated immune response may be involved in the protective effect of Que on INH hepatotoxicity, which still needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the SIRT1/ERK pathway was essential for Que protecting against INH‐induced apoptosis. In addition to apoptosis, immune response is another important feature in INH‐induced hepatotoxicity and SIRT1/ERK is also known as a potential regulator of immune process . Hence, SIRT1/ERK‐mediated immune response may be involved in the protective effect of Que on INH hepatotoxicity, which still needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles described effects on cells involved in the immune system, macrophages, and T cells. Beneficial effects on autoimmune diseases and graft rejection problems can be envisioned from these cell assays, for example through reduction of effector T cell proliferation and differentiation 57,69 , and increase in the number and suppressive function of T regulatory cells Tregs (see Chapter undefined for in vivo results) 64 .…”
Section: Sirtuinmentioning
confidence: 99%
“…The important role played by this enzyme in B- and T cell interaction during the development of GvHD was recently highlighted by Daenthanasanmak et al . ( 165 ). In a murine model, the authors demonstrated that donor T cells lacking sirt1 reduced B cell activation and differentiation but increased Tregs.…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%
“…In a murine model, the authors demonstrated that donor T cells lacking sirt1 reduced B cell activation and differentiation but increased Tregs. Moreover, administration of the sirt1 inhibitor selisistat (EX 527) resulted in reduced Tfh responses along with preventing and treating cGvHD by downregulation of IFN-γ, IL-17, and IL-21, which have all been associated with cGvHD pathogenesis ( 165 );…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%